Towards a Ge-Sb-Se/S hyperspectral imaging probe for early cancer diagnosis - Parnell, Harriet (2018)
Owing to their vitreous nature and mid-infrared (MIR) transparency, chalcogenide glasses are a promising material for remote hyperspectral imaging. For medical applications, such as in-vivo cancer diagnosis, Ge-Sb-Se glasses are a particularly interesting material since, it is believed that Sb-containing chalcogenides are less toxic than their As-containing equivalents. For passive optical fibres which aim to deliver and collect MIR light to and from tissue samples, the main challenge which faces their performance is the removal of extrinsic optical losses. Hence, this Project explores and develops high purity Ge-Sb-Se/S bulk glasses and optical fibres. Focussing on the GexSb10Se90-x atomic % (at. %) glass series, bulk samples are initially characterised before the fibre-drawing capability of each composition is assessed. Although stoichiometric Ge25Sb10Se65 at. % and non-stoichiometric Ge20Sb10Se70 at. % glasses both exist within the same two-dimensional, overconstrained network, results from their fibre-drawing investigations reveal a significant difference in their resistance against crystallisation. Whereas, non-stoichiometric Ge20Sb10Se70 at. % is shown to produce stable optical fibres with promising low losses, it is found that stoichiometric Ge25Sb10Se65 at. % repeatedly crystallises into a single phase of monoclinic GeSe2.